2020
DOI: 10.1063/1.5131562
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput electrochemical sensing platform for screening nanomaterial–biomembrane interactions

Abstract: Article:Owen, J orcid.org/0000-0003-0778-0858, Kuznecovs, M, Bhamji, R et al. (7 more authors) (2020) High-throughput electrochemical sensing platform for screening nanomaterial-biomembrane interactions. Review of Scientific Instruments, 91 (2). 025002. AbstractA high-throughput, automated screening platform has been developed for the assessment of biological membrane damage caused by nanomaterials. Membrane damage is detected using the technique of analysing capacitance-current peak changes obtained through r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…CFD simulations of fluid flow at a flow rate of 100 μL h −1 and species transport through the microfluidic channel, using the methodology applied to study flow through a similar microfluidic geometry by the authors, [ 96 ] confirmed no undesirable flow characteristics were observed in the microfluidic channel and cell cavity. The concentration of species within the cavity reached that of the inflow concentration after approximately 700 s, a short time compared to the overall timescale of the exposure period (24 h) during an experiment.…”
Section: Methodsmentioning
confidence: 98%
“…CFD simulations of fluid flow at a flow rate of 100 μL h −1 and species transport through the microfluidic channel, using the methodology applied to study flow through a similar microfluidic geometry by the authors, [ 96 ] confirmed no undesirable flow characteristics were observed in the microfluidic channel and cell cavity. The concentration of species within the cavity reached that of the inflow concentration after approximately 700 s, a short time compared to the overall timescale of the exposure period (24 h) during an experiment.…”
Section: Methodsmentioning
confidence: 98%
“…All other reagents were of analytical grade and purchased from Sigma-Aldrich. The microfabricated platinum electrodes [20,21,42,43] were supplied by the Tyndall National Institute (Cork, Ireland). Hg was electrodeposited on the Pt disc of radius 0.480 mm to give a Pt/Hg electrode as described previously [20,21,42,43].…”
Section: Methodsmentioning
confidence: 99%
“…Membrane-on-chip microplatforms emerge for high throughput membrane sensing, giving information of the events happening on a supported cellular membrane. The most used membrane biosensing microtechnology comprises electrochemical sensors fabricated with self-assembled monolayers supported on mercury electrodes that provide information of the interactions or damage on the membrane (Owen et al, 2020;Rashid et al, 2017). Recently, Owen et al reported an automated, rapid and HTP sensing microfluidic platform for the screening of nanomaterial-biomembrane interactions (Owen et al, 2020).…”
Section: Nanotoxicologymentioning
confidence: 99%
“…The most used membrane biosensing microtechnology comprises electrochemical sensors fabricated with self-assembled monolayers supported on mercury electrodes that provide information of the interactions or damage on the membrane (Owen et al, 2020;Rashid et al, 2017). Recently, Owen et al reported an automated, rapid and HTP sensing microfluidic platform for the screening of nanomaterial-biomembrane interactions (Owen et al, 2020). The integrated microfluidic device provided electrochemical information of the interactions of chlorpromazine and citrate coated gold nanomaterial with 1,2-dioleoyl-sn-glycero-3-phosphocoline membranes, supposing an easy-to-use interface to assess cytotoxicity based on membrane damage (less than 6 min per assay).…”
Section: Nanotoxicologymentioning
confidence: 99%